A rare case of Goldenhar syndrome: oculo-auriculo-vertebral spectrum - Pradeep, Pooja; Umapathi, Nandhinee; S., Jagadeeshwari; S., Sundari; Shylaja, D. (International Journal of Contemporary Pediatrics, 2019)
Franceschetti-Goldenhar syndrome or Goldenhar syndrome, also known as facio-auricular-spectrum (FAV), first and second branchial arch syndrome, or Oculo-Auriculo-Vertebral (OAV) spectrum is a rare congenital malformation which encompasses various morphological and functional abnormalities. The incidence of Goldenhar syndrome has been reported between 1:3500 to 1:5600 children, with a male: female ratio of 3:23. The incidence is higher, about 1 in 1000 children with congenital deafness. The exact etiology is not known. However, it is possible that abnormal embryonic vascular supply, disrupted mesodermal migration or some other factors leads to defective formation of the brachial and vertebral system. Most of the cases have been sporadic. Autosomal dominant, autosomal recessive and multifactorial modes of inheritance have also been suggested. Chromosomal studies have not revealed any abnormality. Authors report a case of a neonate with hemifacial microsomia, bilateral cleft lip and cleft palate, right deformed pinna, right facial palsy, single umbilical artery and congenital heart disease.